Genetic analyses of HIV env associated with uveitis in antiretroviral-naive individuals. (24th August 2017) - Williams-Wietzikoski, Corey A.; So, Isaac D.; Bull, Marta E.; Samleerat, Tanawan; Pathanapitoon, Kessara; Kunavisarut, Paradee; Kongyai, Natedao; Ngo-Giang-Huong, Nicole; Frenkel, Lisa M.; Sirirungsi, Wasna
Abstract : Objective: To analyze and compare HIV-1 env sequences from the eye to those from the blood of individuals with uveitis attributed to HIV with the goal of gaining insight into the pathogenesis of HIV-associated eye disease. Design: A prospective case series of five HIV-infected antiretroviral-naive individuals with uveitis negative for other pathogens. Methods: RNA from blood plasma and ocular aqueous humor was reverse transcribed using random hexamers. HIV env C2-V5 (HXB2: 6990–7668) sequences were generated by single-genome amplification using nested polymerase chain reaction followed by bidirectional Sanger sequencing. Sequence analyses by Geneious, Geno2Pheno, N -GLYCOSITE, DIVEIN, and HyPhy evaluated relationships between HIV in plasma and aqueous humor. Results: A median of 20 (range: 13–22) plasma and 15 (range: 9–18) aqueous humor sequences were generated from each individual. The frequencies of sequences with predicted- N -linked-glycosylation sites and C-X-C chemokine receptor type 4 were comparable in aqueous humor and plasma of all five patients. Aqueous humor sequences had lower median genetic diversity compared with plasma across all patients, but similar divergence, in four of five patients. Aqueous humor HIV sequences were compartmentalized from plasma across subjects by Critchlow correlation coefficient, Slatkin and Maddison, nearest-neighbor statistic, and Fixation index. Conclusion: Among antiretroviral-naive individuals with uveitis attributed to HIV, the universal compartmentalization and decreased diversity of eye compared with blood sequences suggests time-limited passage of a small subset of variants from each patient's viral population into the eye tissues, followed by limited immune selection despite the inflammatory uveitis. Abstract : Supplemental Digital Content is available in the text